Breeding experience improves reproductive outcomes in an avian conservation breeding program - Flanagan, A. M.; Masuda, B.; Swaisgood, R. R. (Frontiers in Conservation Science, 2025)
In the midst of Earth’s sixth mass extinction, conservation breeding can serve as a vital component of critically endangered species recovery. The effect of an individual or pair’s breeding experience on fitness has been evaluated across numerous avian taxa, but research on how experience impacts breeding outcomes for critically endangered birds in human care is scarce. In this retrospective study, we examined whether breeding experience impacted reproductive success in a conservation breeding program (CBP) for the last remaining and critically endangered Hawaiian corvid, the ‘Alalā (Hawaiian crow, Corvus hawaiiensis). We evaluated whether experience was predictive of nest quality, clutches, fertilized eggs, and incubation. We determined that breeding experience positively impacted all reproductive stages, except for egg fertilization. Our results can be used to inform breeding pair selection, for example, pairing an Expert with an inexperienced individual may lead to better reproductive outcomes compared to pairing two Novice individuals. Broadly, our study presents an approach for quantitatively evaluating experience effects on reproduction in CBPs and showcases the value of leveraging routinely collected data to facilitate evidence-based decisions, that will lead to optimizing the conservation value of a CBP through maximizing reproductive success.